2015
DOI: 10.1016/j.juro.2015.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Surgical Margin Status by Surgical Approach among Patients Undergoing Partial Nephrectomy for Small Renal Masses

Abstract: Laparoscopic and robotic partial nephrectomy is associated with higher positive surgical margin rates compared to open partial nephrectomy for clinical T1a renal cell carcinoma. The effect of margin status on long-term oncologic outcomes in this context remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
3
37
0
7
Order By: Relevance
“…Only two comparative studies showed significant differences in terms of PSM rate between different surgical approaches. Specifically, Tabayoyong et al reported lower PSMs rate in patients who underwent OPN compared with those receiving a minimally invasive approach [22]. Similarly, Zargar et al reported a lower PSMs rate in OPN compared with RAPN [11].…”
Section: Resultsmentioning
confidence: 99%
“…Only two comparative studies showed significant differences in terms of PSM rate between different surgical approaches. Specifically, Tabayoyong et al reported lower PSMs rate in patients who underwent OPN compared with those receiving a minimally invasive approach [22]. Similarly, Zargar et al reported a lower PSMs rate in OPN compared with RAPN [11].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐four eligible studies included 60 808 patients who underwent PN, of whom 19 638 underwent RaPN with mean age 58.9 years and 41 170 underwent OPN with mean age 58.5 years. Table presents the baseline patient demographics of all enrolled studies.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of PSM in nephron-sparing techniques has been reported to be in the range of 4.9–8.1% for the open and laparoscopic approaches. 22 PSM range has been reported to be 0–8.7% for the robotic approach. 1016,22 In our series, we did not encounter any PSMs in the final pathology.…”
Section: Discussionmentioning
confidence: 99%
“…22 PSM range has been reported to be 0–8.7% for the robotic approach. 1016,22 In our series, we did not encounter any PSMs in the final pathology. Several intra-operative techniques can aid in accomplishing the above-mentioned goal of achieving negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%